Wada asymmetry in patients with drug‐resistant mesial temporal lobe epilepsy: Implications for postoperative neuropsychological outcomes. Issue 3 (6th August 2018) - Sever, Ryan W.; Vivas, Andrew C.; Vale, Fernando L.; Schoenberg, Mike R.
Summary: Objective: This study reports neuropsychological outcomes based on preoperative Wada testing in patients with drug‐resistant mesial temporal lobe epilepsy (mTLE). Methods: Patient records were retrospectively reviewed as part of a larger database. Patients with a diagnosis of TLE based on seizure semiology and long‐term surface video–electroencephalography (EEG) were identified. These patients underwent preoperative and postoperative testing including advanced imaging (magnetic resonance imaging [MRI]), Wada testing, and neuropsychological assessment. Decrements in neuropsychological function were noted in comparison of pre‐ and postoperative studies. Patients had regular follow‐up in the multidisciplinary epilepsy clinic to assess seizure outcomes. All participants had Engel class I/II outcome following selective amygdalohippocampectomy (AH) via the inferior temporal gyrus (ITG) approach. Results: Forty‐eight patients with electrographic and clinical semiology consistent with unilateral mTLE were identified. Left mTLE was identified in 28 patients (58.3%), whereas 20 patients (41.7%) had right mTLE. Language‐dominant hemisphere resections were performed on 23 patients (47.9%) (all left‐sided surgery), whereas 25 (52.1%) had language nondominant resection (all right‐sided and five left‐sided surgery). Twenty‐two participants (45.8%) showed no Wada memory asymmetry (No‐WMA), whereas 26 (54.2%) exhibited Wada memory asymmetry (WMA). Postoperatively, analysis of variance (ANOVA) found that the No‐WMA group exhibited a decline in verbal memory, but average scores on measures of nonverbal reasoning, general intelligence, and mood improved. Alternatively, patients with WMA did not show declines in memory postoperatively, and also exhibited improved nonverbal reasoning and general intelligence. Neither group exhibited reliable decline in verbal fluency or visual confrontation naming. Significance: Wada procedures for predicting surgical outcome from elective temporal surgery have been criticized and remain an area of active debate. However, decades of data across multiple epilepsy centers have demonstrated the value of Wada for reducing unanticipated neuropsychological adverse effects of surgical treatment. These data show that no Wada memory asymmetry increases the risk for neuropsychological decline following ITG approach for selective AH for drug‐resistant mTLE.